Severe nutritional anemia among hospitalized children in Central India – Descriptive study - Bokade, CM; Kulkarni, Spurti; Singh, Nikita; Tirpude, Bhagyashree; Nawlakhe, Ketaki (Indian Journal of Child Health, 2024)
Despite numerous efforts, pediatric nutritional anemia remains one of the most serious health issues in developing countries. Severe nutritional anemia is associated with a number of modifiable risk factors, which can be overcome if the risk factors are accurately identified and addressed for different population groups. The purpose of this descriptive study is to focus on severe nutritional anemia in hospitalized children aged 1–5 years in a tertiary care center in Central India. Hospitalized children were enrolled in the study, and demographic, socioeconomic, clinical, and laboratory data, as well as clinical and laboratory images, were reviewed. For defining severe anemia, the World Health Organization cutoff value was used. Out of total 9850 children of 1–5 years of age group admitted in hospital for 2 years, 197 children had severe nutritional anemia, indicated the incidence of 2%. Lower socioeconomic status and malnutrition were significantly correlated to severe nutritional anemia.